Functionality and acceptability of a wireless fetal heart rate monitoring device in term pregnant women in rural Southwestern Uganda - Mugyenyi, Godfrey Rwambuka; Atukunda, Esther Cathyln; Ngonzi, Joseph; Boatin, Adeline; Wylie, Blair J.; Haberer, Jessica E. (BMC Pregnancy and Childbirth, 2017)
Background: Over 3 million stillbirths occur annually in sub Saharan Africa; most occur intrapartum and are largely preventable. The standard of care for fetal heart rate (FHR) assessment in most sub-Saharan African settings is a Pinard Stethoscope, limiting observation to one person, at one point in time. We aimed to test the functionality and acceptability of a wireless FHR monitor that could allow for expanded monitoring capacity in rural Southwestern Uganda. Methods: In a mixed method prospective study, we enrolled 1) non-laboring healthy term pregnant women to wear the device for 30 min and 2) non-study clinicians to observe its use. The battery-powered prototype uses Doppler technology to measure fetal cardiotocographs (CTG), which are displayed via an android device and wirelessly transmit to cloud storage where they are accessible via a password protected website. Prototype functionality was assessed by the ability to obtain and transmit a 30-min CTG. Three obstetricians independently rated CTGs for readability and agreement between raters was calculated. All participants completed interviews on acceptability. Results: Fifty pregnant women and 7 clinicians were enrolled. 46 (92.0%) CTGs were successfully recorded and stored. Mean scores for readability were 4.71, 4.71 and 4.83 (out of 5) with high agreement (intra class correlation 0. 84; 95% CI 0.74 to 0.91). All pregnant women reported liking or really liking the device, as well as high levels of comfort, flexibility and usefulness of the prototype; all would recommend it to others. Clinicians described the prototype as portable, flexible, easy-to-use and a time saver. Adequate education for clinicians and women also seemed to improve correct usage and minimise concerns on safety of the device. Conclusions: This prototype wireless FHR monitor functioned well in a low-resource setting and was found to be acceptable and useful to both pregnant women and clinicians. The device also seemed to have potential to improve the experience of the users compared with standard of care and expand monitoring capacity in settings where bulky, wired or traditional equipment are unreliable. Further research needs to investigate the potential impact and cost of such innovations to improve perinatal outcomes.
Keywords: Sense4Baby; Wireless fetal monitor; Electronic fetal monitoring